Penerapan Metode Reliability Centered Maintenance (RCM) dan Fault Tree Analyze (FTA) Pada Mesin Cetak Lembar [Studi Kasus Percetakan XYZ Di Cikarang] - Rahardjo, Sugeng Budi; Widya, Adi Rusdi (JURNAL TEKNIK INDUSTRI, 2021)
The technological disruptions that have occurred over the past few decades have inevitably affected the printing industry especially the mass media printing industry. Print media with products such as: Books, Magazines, Newspapers, Tabloids, will definitely be affected. The product was eliminated by digital media, not to mention, the covid pandemic that occurred in the last two years also triggered a sharp decline in the media business. The eight-color KBA machine, which is the focus of this research, is a ten-year-old machine with excellent printing capabilities, namely high capacity, 4-color alternating printing capability, and automatic machine control. Deteriorating machine life, as well as maintenance, functional audits and upgrades are key factors. Problems that often arise are print units, infeed, and control units, resulting in downtime and delays in the production process so that machine performance becomes less effective. The purpose of this research is to determine the maintenance interval schedule and find out the maintenance actions or activities that need to be carried out. To overcome the problem in this study using the method of Reliability Centered Maintenance (RCM), Fault Tree Analysis (FTA) with the calculation of Failure Modes and Effects Analyze (FMEA). RCM is defined as the process used to determine what must be done for machine maintenance, while FMEA is defined as the method for identifying the highest form of failure for each machine fault that occurs. From the calculation results using FMEA, FTA and RCM obtained the maintenance interval results on the Cylinder Section components with a maintenance interval of 10.58 hours.